Implementasi Kebijakan Transformasi Perpustakaan Berbasis Inklusi Sosial dalam Meningkatkan Literasi Masyarakat di Kabupaten Bangka Barat - Eka Octawianto; Darol Arkum; Raniasa Putra; Yan Megawandi (PERSPEKTIF, 2026)
The development of information technology requires libraries to adapt to remain relevant as a center for community learning. One of the efforts made is through a social inclusion-based library transformation policy that places libraries not only as information providers, but also as spaces for community empowerment. This study aims to analyze the implementation of library transformation policies based on social inclusion at the West Bangka Regency Library and Archives Office and identify the factors that affect it. The research uses a qualitative approach with a descriptive method through observation, in-depth interviews, and documentation, and is analyzed using the perspective of George Edward III's policy implementation which includes communication, resources, disposition, and bureaucratic structure. The results of the study show that the implementation of the policy has gone quite well, characterized by the replication of the program to the village level and the increasing role of the library as a community learning space. However, the effectiveness of implementation still faces obstacles in the form of limited human resources, lack of optimal policy communication, weak cross-sector coordination, and the absence of adequate regional regulations and monitoring systems. Therefore, strengthening governance, institutional capacity, and derivative policy support is needed to ensure the sustainability of library transformation based on social inclusion.